Disrupted homeostasis in sickle cells: Expanding the comprehension of metabolism adaptation and related therapeutic strategies - Bernardo, Victoria Simões [UNESP]; Torres, Flaviene Felix [UNESP]; Zucão, Ana Clara Albertin [UNESP]; Chaves, Nayara Alves [UNESP]; Santana, Ilana Luize Rocha [UNESP]; da Silva, Danilo Grünig Humberto [UNESP] (Elsevier, 2025)
Sickle cell disease (SCD) is a hereditary hemolytic anemia associated with the alteration of the membrane composition of the sickle erythrocytes, the loss of glycolysis, dysregulation of the pyruvate phosphatase pathway, and changes in nucleotide metabolism of the sickle red blood cell (RBC). This review provides a comprehensive overview of the impact of the presence of Hb S, which leads to the disruption of the normal RBC metabolism. The intricate interplay between the redox and energetic balance in erythrocytic cells, where the glycolysis, pentose phosphate pathway, and methemoglobin reductase pathways are all altered in sickle RBC, is a key focus. Moreover, this review summarizes the current knowledge about the disease-modifying agents and their action mechanisms based on the sickle RBC alterations previously mentioned (i.e., their association with beneficial effects on the sickle cells' membrane, to their RBCs' energy metabolism, and to their oxidative status). Therefore, providing a comprehensive understanding of how sickle cells cope with the disruption of metabolic homeostasis and the most promising therapeutic agents able to ameliorate the various consequences of abnormal sickle RBC alterations.
Keywords: Antioxidant capacity; Erythrocyte metabolism; Hemoglobin S; Sickle cell disease